The Optic Tectum of Birds: Mapping Our Way to Understanding Visual Processing. - Wylie, Douglas R. W.; Gutierrez-Ibanez, Cristian; Pakan, Janelle M. P.; Iwaniuk, Andrew N. (Canadian Journal of Experimental Psychology, 2009)
Over the past few decades there has been a massive amount of research on the geniculo-striate visual system in primates. However, studies of the avian visual system have provided a rich source of data contributing to our understanding of visual processing. In this paper we review the connectivity and function of the optic tectum (homolog of the superior colliculus) in birds. We highlight the retinotopic projections that the optic tectum has with the isthmal nuclei, and the functional topographic projections that the optic tectum has with the nucleus rotundus and entopallium (homologs of the pulvinar and extrastriate cortex, respectively) where retinotopy has been sacrificed. This work has been critical in our understanding of basic visual processes including attention, parallel processing, and the binding problem. Reprinted by permission of the publisher.